Efficient process for recovery of waste LiMn2O4 cathode material precipitation thermodynamic analysis and separation experiments. (15th July 2020) - He, Shichao; Liu, Zhihong
Graphical abstract: Highlights: Precipitation thermodynamic analysis on the sulphate solution systems are undertaken. The products of MnCO3 and Li2 SO4 are obtained. The Mn and Li present in the waste LiMn2 O4 cathode material are completely recovered. Abstract: An efficient process is proposed for recovery of waste LiMn2 O4 cathode material, which is one of the most commonly used cathode materials in LIBs. This report constitutes the precipitation thermodynamic analysis and separation experiments based on the water-leaching solutions during the processes of low-temperature calcination with (NH4 )2 SO4 and water-leaching. Precipitation thermodynamic analysis is undertaken to investigate the effects of initial concentration of the target solution, [N]T1, excess precipitant, and addition of (NH4 )2 SO4 on the manganese precipitation in the Mn 2+ –Li + –SO4 2− –NH3 –NH4 + –CO3 2− –H2 O system. Moreover, the effects of initial concentration of the target solution, [N]T2, and excess precipitant on the lithium precipitation in the Li + –SO4 2− –NH3 –NH4 + –CO3 2− –H2 O system are investigated. All these factors clearly influence the manganese and lithium precipitation, particularly the [N]T and the presence of excess precipitant in the system. The precipitation experimental results demonstrate that the optimal conditions are: a precipitation temperature of 35 °C; an excess coefficient of the precipitant of 2.4; the use of NHC-3 to precipitate the ML-3 solution; a maximum precipitation percentage of manganese of 99.96%; and an absence of Li2 CO3 precipitation. The double-sulfate salts (Li(NH4 )SO4 & (NH4 )2 SO4 ) evaporated and crystallised from the Li + /NH4 + solution are mixed with the waste LiMn2 O4 cathode material for calcination and water leaching, for which the efficiencies of Li and Mn are 100% and 96.89%, respectively. The double-sulfate salts are calcined at 550 °C for 45 min to obtain the Li2 SO4 product. Finally, the complete recovery and separation of Mn and Li in the waste LiMn2 O4 cathode material are achieved.